Pengaruh Literasi Digital dan Pemanfaatan Aplikasi Akuntansi terhadap Efektivitas Sistem Informasi UMKM dengan Kompetensi Pengguna sebagai Variabel Mediasi - Alda Rahmadhini; Suwandi, Suwandi (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to test the influence of digital literacy and the use of accounting applications on the effectiveness of MSME information systems with user competence as a mediating variable. The research sample amounted to 100 MSME actors in Gresik City who were selected using purposive sampling techniques according to the research criteria. Data testing was carried out using a quantitative approach using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method through the SmartPLS application. The results of the study show that digital literacy and the use of accounting applications have a positive effect on the effectiveness of MSME information systems. Meanwhile, user competence does not have a significant effect and is unable to mediate the influence of digital literacy and the use of accounting applications on the effectiveness of information systems. This research is expected to provide benefits for MSME actors in increasing the use of digital technology and accounting applications, as well as become an academic reference for future research. The limitations of this study lie in the scope of the MSME scale, which has not considered external factors, and the research model that has not fully explained the role of user competence as a mediating variable.